Encyclopedia of journalism - Sterling, Christopher H. 1943- (Gale virtual reference library, 2009)
Covers all significant dimensions of journalism, including print, broadcast, and Internet journalism; U.S. and international perspectives; history; technology; legal issues and court cases; ownership; and economics.